Предмет: Алгебра,
автор: Infinity8881
Упростить:
cos^3(pi/12) + sin^3(pi/12)
Ответы
Автор ответа:
2
cos^3(pi/12) + sin^3(pi/12)=
(cos(pi/12) + sin(pi/12)) (cos^2(pi/12) -cos(pi/12) sin(pi/12) +sin^2(pi/12))=
=(cos(pi/12) + sin(pi/12)) (1-1/2sin(pi/6)=(√((cos(pi/12) + sin(pi/12))^2) 3/4=
=3/4[√(1+2cos(pi/12) sin(pi/12)]=3/4 [√(1+ sin(pi/6))]=3/4[√(1+1/2)]=3/4[√(3/2)]
(cos(pi/12) + sin(pi/12)) (cos^2(pi/12) -cos(pi/12) sin(pi/12) +sin^2(pi/12))=
=(cos(pi/12) + sin(pi/12)) (1-1/2sin(pi/6)=(√((cos(pi/12) + sin(pi/12))^2) 3/4=
=3/4[√(1+2cos(pi/12) sin(pi/12)]=3/4 [√(1+ sin(pi/6))]=3/4[√(1+1/2)]=3/4[√(3/2)]
Похожие вопросы
Предмет: Алгебра,
автор: fisenkonasta312
Предмет: Биология,
автор: lifelera3
Предмет: Алгебра,
автор: alekywsejmanuev26
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: semenovvlad090